Mouse Oct-1 contains a composite homeodomain of human Oct-1 and Oct-2. - Suzuki, N (1993)
Members of the Oct family of transcription factors specifically interact with the octamer motif, ATGC-AAAT, a regulatory element important for tissue- and cell-specific transcription as well as for the expression of housekeeping genes. Except for Oct-1, all Oct factors are expressed in a temporally and spatially restricted mode during murine development and their number varies in a given cell type. Despite its ubiquitous expression pattern Oct-1 may play a role in murine development. As a first step towards elucidating the role of Oct-1 we report the complementary DNA cloning of the mouse Oct-1 gene. Two large transcripts of 5 and 14 kb are derived from a single gene. The expression patterns of three splicing products of Oct-1 are similar in a number of cells and tissues. In the POU region murine Oct-1 differs in four amino acids from the human homologue and these differences are restricted to helices 1 and 2. Interestingly, two of the four variant amino acids are identical to those in human and mouse Oct-2 and thus the murine Oct-1 homeodomain is intermediary in sequence between human Oct-1 and Oct-2. These two amino acids together with a third one have been shown to be relevant for the interaction between human Oct-1 and herpes simplex virus transactivator VP16. Nevertheless, VP16 interacts albeit weakly with murine Oct-1. We speculate that the differences in the human and mouse Oct-1 homeodomains reflect host-specific differences in protein-protein interactions.